2013
DOI: 10.1108/afr-10-2012-0058
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating grain producers' production financing alternatives: evidence from South Africa

Abstract: Purpose -The purpose of this paper is to identify, present and compare agricultural production financing alternatives available to grain producers in South Africa. From the South African perspective, agricultural land cannot always be utilised as collateral and therefore alternative financing has developed. Design/methodology/approach -The study makes use of an exploratory study by applying qualitative techniques. The research population was agricultural finance providers in South Africa and semi-structured in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…As collateral is a regular ingredient of risky lending, it serves to limit potential losses for financiers (Menkhoff et al, 2012). Within the South African context, traditionally the balance sheet lending approach is followed, where the financier generally takes out a lien on the producer's land, which serves as collateral for the value of the producer's loan (Middelberg, 2013). In addition, or alternatively, the financier might require the following, or a combination thereof, to serve as collateral for a production loan including: i) crop insurance, either limited peril insurance or multiple peril crop insurance; ii) a cession on non-current assets excluding land; and/or iii) the expected harvest.…”
Section: 3mentioning
confidence: 99%
See 1 more Smart Citation
“…As collateral is a regular ingredient of risky lending, it serves to limit potential losses for financiers (Menkhoff et al, 2012). Within the South African context, traditionally the balance sheet lending approach is followed, where the financier generally takes out a lien on the producer's land, which serves as collateral for the value of the producer's loan (Middelberg, 2013). In addition, or alternatively, the financier might require the following, or a combination thereof, to serve as collateral for a production loan including: i) crop insurance, either limited peril insurance or multiple peril crop insurance; ii) a cession on non-current assets excluding land; and/or iii) the expected harvest.…”
Section: 3mentioning
confidence: 99%
“…Although alternative financing models have been developed, using both the expected harvest and crop insurance as collateral, the use of agricultural land as collateral in providing financing to producers is still the primary and cheaper form of financing (Middelberg, 2013;Anseeuw & Ducastel, 2012). However, to place a value on the collateral, the agricultural financier has to value the agricultural land and this valuation process is intricate and complex (Wessels & Willemse, 2013;Garcia & Grande, 2003;Cabrido, 1990).…”
Section: Introductionmentioning
confidence: 99%
“…Usefulness of financial information is problematic when being discussed in the farming context because Australian farms must record and report financial transactions for taxation purposes, and decision making is not a function of compliance reporting (Marriott and Marriott, 2000). This perhaps explains why a number of studies across a number of countries have consistently found that farmers find financial information not very useful and very difficult to understand (Argilés and Slof, 2003;Halabi et al, 2010;Wolf et al, 2011;Middelberg, 2013).…”
Section: Introductionmentioning
confidence: 99%